The Culture of sentiment : race, gender, and sentimentality in nineteenth-century America - Samuels, Shirley (OUP E-Books., 1992)
This collection of critical essays endeavours to give fuller body and scope to the subject of 19th-century American sentimentality by examining it in light of the so-called "women's culture" and the issue of race